Keefektifan Penggunaan Dekak-dekak dalam Pembelajaran Matematika di Sekolah Dasar - Suharjo Suharjo (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Effectiveness of the Abacus Use in Mathematics Instruction at the Elementary School. This classroom action research was designed to examine the effectiveness of using abacus usage to improve students comprehension on addition and subtraction in story problems. The study involved 1 teacher and 32 students of the Elementary-Laboratory School (SD Laboratorium), State University of Malang. The results showed that the abacus use could improve the students comprehension in learning addition and subtraction stated in story problems. The students mean score was increased from 59.30 in 1st cycle to 78.13 in 2nd cycle.